2008
DOI: 10.1038/onc.2008.451
|View full text |Cite
|
Sign up to set email alerts
|

Id-1 activates Akt-mediated Wnt signaling and p27Kip1 phosphorylation through PTEN inhibition

Abstract: Inhibitor of differentiation-1 (Id-1) has been accepted as a putative oncogene to promote oncogenic processes through inactivation of tumor suppressors and activation of growth promoting pathways. Here, we show that Id-1 activates the Akt pathway by inhibition of phosphatase and tensin homologue deleted on chromosome 10 (PTEN) transcription through downregulation of p53. Id-1 negatively regulated both p53 and PTEN at the transcriptional level. In promoter assay with serial deletion and chromatin immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 21 publications
4
44
0
Order By: Relevance
“…28 Id1 has also been shown to enhance endothelial progenitor cell-driven angiogenesis in ovarian cancer, an effect mediated largely by the PI3K/AKT signaling pathway. 29,30 We have determined that Id1 physically interacts with AKT1, through its C-terminal region, and promotes AKT1 phosphorylation; this is consistent with the decrease in PI3K/p110g phosphorylation induced by loss of Id1, and it contrasts with the transcriptional effects of Id1, which depend on its bHLH domain, a domain not required for its interaction with AKT1. Moreover, Id2 and Id3, which both have bHLH domains, do not bind AKT1, together indicating that Id1 regulates AKT signaling through mechanisms distinct from its transcriptional effects.…”
Section: Discussionmentioning
confidence: 71%
“…28 Id1 has also been shown to enhance endothelial progenitor cell-driven angiogenesis in ovarian cancer, an effect mediated largely by the PI3K/AKT signaling pathway. 29,30 We have determined that Id1 physically interacts with AKT1, through its C-terminal region, and promotes AKT1 phosphorylation; this is consistent with the decrease in PI3K/p110g phosphorylation induced by loss of Id1, and it contrasts with the transcriptional effects of Id1, which depend on its bHLH domain, a domain not required for its interaction with AKT1. Moreover, Id2 and Id3, which both have bHLH domains, do not bind AKT1, together indicating that Id1 regulates AKT signaling through mechanisms distinct from its transcriptional effects.…”
Section: Discussionmentioning
confidence: 71%
“…(B) Id1 expression in breast cancer cells is induced by cyclooxygenase-2-derived prostaglandin E2 (promoting metastasis) while is repressed by KLF17 (a metastatic suppressor) [51,52]. Id1 expression may negatively regulate PTEN, leading to Akt activation, and drives tumor reinitiation during breast cancer metastasis [53][54][55][56]. (C) In endothelial progenitor cells Id1 and Id3 maintain the expression of FGFR1, MMP2, laminin 5 and alpha 6-beta 4 integrin [57], thereby enabling the mobilization of EPC from the bone marrow to the site of the tumor in response to circulating cytokines [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2007a) first reported that Id-1 activates the PI3K/Akt pathway, leading to cellular proliferation in esophageal cancer cells. Further, we have demonstrated Id-1 activates the PI3K/Akt-mediated Wnt signaling pathway by PTEN inhibition in MCF-7 cells (Lee et al, 2009). In this study, this mechanism is also proven by an animal model.…”
Section: Discussionmentioning
confidence: 62%
“…As described above, we previously demonstrated that Id-1 plays a role as an activator of the PI3K/Akt pathway and its downstream effectors by PTEN inhibition that is associated with the regulation of cell cycle progression and cellular proliferation (Lee et al, 2009). In the present study, we examined other pathways including TGF-b, BMP-2, and RAR-b as well as FGF3, all of which are known to be regulators of mammary gland development via activation of the Wnt pathway, using RT-PCR (Fig.…”
Section: Morphologic Analysis Of Mammary Glands and Western Blot In Wmentioning
confidence: 90%